A new extended state observer for uncertain nonlinear systems - Ran, Maopeng (2022)
Extended state observer (ESO) is a class of high-gain observers and a powerful tool for output feedback control of uncertain nonlinear systems. In this paper, we propose a new ESO design technique which is based on cascading a series of first-order ESOs. Benefited from the cascade design, saturations can be inserted into the observer internal variables to limit the maximal implemented gain. The convergence of the new ESO with a class of nonlinear gain functions is established, and it is shown that adopting appropriate nonlinear gain mechanisms leads to improvement in measurement noise tolerance. What is more, the new ESO based output feedback control has stronger uncertainty estimation and compensation capability than the standard ESO based output feedback control. Specifically, the proposed approach only relies on the knowledge of the control direction of the uncertain nonlinear system. Finally, the obtained results are applied to suppress the wing rock motion of a slender delta wing.